ANALISIS SITUASI INDUSTRI HILIR KAKAO PASCA PENGENAAN PAJAK EKSPOR KAKAO SEPANJANG TAHUN 2013-2017 (Jurnal Inovisi (Teknik Industri), 2018)
AbstractThe development of the downstream cocoa industry is a serious concern for the government. Various policies in the upstream sector have succeeded in increasing cocoa bean production. The policies in the upstream sector have not had an impact on increasing the downstream cocoa industry. One of the policies launched by the government is an increase in export tax or export duty for cocoa beans. This paper aims to analyze the downstream industry situation after the imposition of export tax on cocoa during 2013-2017. The analysis uses descriptive statistics to show an increase in investment in the downstream cocoa industry and an impact on increasing the price of cocoa beans. The largest increase in the downstream cocoa industry (70%) was given by foreign investment (PMA) which was suspected to be in order to secure industrial supplies in the irrespective countries in the context of the Global Value Chain. The Indonesian government need stop repare a downstream industrial strategy that involves smal land medium industries. Keywords: cocoa, downstream industry, cocoa export tax AbstrakPengembangan industri hilir kakao menjadi perhatian yang serius bagi pemerintah.  Berbagai  kebijakan  di  sektor hulu berhasil meningkatkan produksi biji kakao. Kebijakan di sektor hulu ini belum memberikan dampak peningkatan industri hilir kakao. Salah satu kebijakan yang diluncurkan oleh pemerintah adalah peningkatan pajak ekspor  atau bea keluar biji kakao. Makalah ini bertujuan menganalisis situasi industri hilir pasca pengenaan pajak ekspor kakao sepanjang tahun 2013-2017. Analisis menggunakan statistik deskriptif untuk menunjukkan adanya penambahan investasi industri hilir kakao dan berdampak pada peningkatan harga biji kakao. Penambahan industri hilir kakao terbanyak (70%) diberikan oleh Penanaman Modal Asing (PMA) yang ditenggarai dalam rangka mengamankan pasokan industri di negara masing-masing dalam rangka Global Value Chain. Pemerintah Indonesia perlu menyiapkan strategi industri hilir yang melibatkan industri kecil dan menengah. Kata kunci: kakao, industri hilir, pajak ekspor kakao